Collaborative Governance on Social Safety Networks During The Pandemic Covid-19 - Angin, Ria; Muhammady, Iffan Gallant El (POLITICO, 2023)
This article discusses collaborative governance between governments institutions and NGOs as well as the community groups to manage the social safety network. We have categorized these activities into two types, government’s JPS and NGO’s JPS. The government's JPS program has been funded by the government budget, but the NGO's JPS has been supported from local non-governmental funds. This study used Narrative Policy Framework (NPF) methods.